"Is it Really Worth it to Get Tested?": Primary Care Patients' Impressions of Predictive SNP Testing for Colon Cancer. Issue 1 (22nd August 2012) - Leventhal, Kara‐Grace; Tuong, William; Peshkin, Beth N.; Salehizadeh, Yasmin; Fishman, Mary B.; Eggly, Susan; FitzGerald, Kevin; Schwartz, Marc D.; Graves, Kristi D.
Abstract: Despite significant progress in genomics research over the past decade, we remain years away from the integration of genomics into routine clinical care. As an initial step toward the implementation of genomic‐based medicine, we explored primary care patients' ideas about genomic testing for common complex diseases to help develop future patient education materials and interventions to communicate genomic risk information. We conducted a mixed‐methods study with participants from a large primary care clinic. Within four focus groups, we used a semi‐structured discussion guide and administered brief pre‐ and post‐ discussion quantitative surveys to assess participants' interest, attitudes, and preferences related to testing and receipt of test results. Prior to the discussion, moderators presented a plain‐language explanation of DNA and genetics, defined "SNP", and highlighted what is known and unknown about the risks associated with testing for SNPs related to colorectal cancer risk. We used the NVIVO 8 software package to analyze the transcripts from the focus group discussions. The majority of participants (75 %) were "very" or "somewhat interested" in receiving information from a colon cancer SNP test, even after learning about and discussing the small and still clinically uncertain change in risk conferred by SNPs. Reported interest in testing was related to degree of risk conferred, personal risk factors, family history, possible implications for managing health /disease prevention and curiosity about genetic results. Most people (85 %) preferred that genetic information be delivered in person by a healthcare or genetics professional rather than through print materials or a computer. These findings suggest that patients may look to genetic counselors, physicians or other healthcare professionals as gatekeepers of predictive genomic risk information.